Impact of a 24/7 multiplex-PCR on the management of patients with confirmed viral meningitis. Issue 6 (December 2021) - Péan de Ponfilly, Gauthier; Chauvin, Anthony; Salmona, Maud; Benmansour, Hanaa; Bercot, Béatrice; Camelena, Francois; Courbin, Virginie; Eyer, Xavier; Lecorche, Emmanuel; Mougari, Faïza; Munier, Anne-Lise; Revue, Eric; et al.
Highlights: ± 50% of pleocytosis are infectious meningitis in emergency departments. 24/7 multiplex-PCR strategy has an impact on rate of hospitalization for patients with confirmed viral meningitis. A CSF WBC threshold of 10 /mm3 is adapted for systematic triggering of multiplex-PCR in adults. Summary Objectives: The relevance of syndromic multiplex-PCR for the etiological diagnosis of meningitis or meningoencephalitis is still a matter of debate. Here, we studied the impact of a 24/7 multiplex-PCR on the management of patients consulting in the emergency department for suspicion of community-acquired meningitis. Methods: We conducted a single-center retrospective study at the Emergency department of Lariboisière University Hospital (Paris, France) including all patients suspected of meningitis. During period 1 (April 2014-March 2017), the molecular assays used for the detection of infectious agents in the cerebrospinal fluid (CSF) were performed during the daytime. During period 2 (April 2017-March 2019), multiplex-PCR (BioFire® Filmarray® Meningitis/Encephalitis Panel [ME], bioMérieux) was performed 24/7. Results: During the periods 1 and 2, 4 100 and 3 574 patients were included and 284 (6.9%) and 308 (8.6%) meningitis were diagnosed, respectively. During the periods 1 and 2, the most common causes of meningitis were enterovirus (23.9% and 29.5%), varicella zoster virus (10.2% and 6.8%) and herpes simplex virus-2 (4.2% and 8.1%). For patients with confirmed viral meningitis, a significant decrease was found between period 1 and period 2, respectively for the rate of hospitalization (73.9% vs 42.0%; p  < 0.05), the length of stay (3[2–5] vs 2[1–3] days; p  < 0.05), the empirical antiviral (26.1% vs 14.5%) and antibacterial administrations (29.3% vs 14.5%; p  < 0.05). Conclusions: Multiplex-PCR is an important tool in the diagnosis of infectious meningitis in the emergency department and is relevant in the management of meningitis by screening for patients who do not require hospitalization and antibacterial therapy.